The Polemics of Interfaith Marriage and Patterns of Negotiation in Indonesian Films - Widyawati, Marta; Fikri Amalia, Anindita; Hamdan Mukafi, Muhammad (Integritas Terbuka: Peace and Interfaith Studies, 2025)
Indonesian cinema has often portrayed the theme of marriage between different religions occasionally. These problems frequently occur in society and trigger a complicated negotiation process between the individuals concerned. The difficulty of negotiation is because religion and marriage have significant consequences for the stability of family and community networks, so decision-making is based on many considerations. The prohibition of marriages of different religions raises questions regarding the compelling ways for couples of various faiths to deal with the inner and physical conflicts caused by these events. This research examines the negotiation patterns of different religious couples in Indonesian films (Ayat-Ayat Cinta 1, Tanda Tanya, and Akhirat: A Love Story). Roland Barthes' semiotic theory and Gordon Allport's theory of religion are used in this study to examine the issue. The research can show how the three films offer a process of contemplation that ultimately leads the characters to make wise decisions and maintain broader harmonization.